Handbook of learning from multiple representations and perspectives - Van Meter, Peggy, 1964-; List, Alexandra, 1988-; Lombardi, Doug, 1965-; Kendeou, Panayiota (Routledge, Taylor & Francis Group, 2020)
"In and out of formal schooling, online and off, today's learners must consume and integrate a level of information that is exponentially larger and delivered through a wider range of formats and viewpoints than ever before. Handbook of Learning from Multiple Representations and Perspectives provides a path for understanding the cognitive, motivational, and socioemotional processes and skills necessary for learners across educational contexts to make sense of and utilize information sourced from varying inputs. Uniting research and theory from education, psychology, literacy, library sciences, media and technology, and more, this forward-thinking volume explores the common concerns, shared challenges, and thematic patterns in our capacity to make meaning in an information-rich society"--
Keywords: vyučovací metody; reprezentace informací; teaching methods; representation of information; kognitivní učení; příručky; sborníky; handbooks and manuals; papers of several authors